2006
DOI: 10.1262/jrd.17055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Maturation Culture Period of Oocytes on the Sex Ratio of In Vitro Fertilized Bovine Embryos

Abstract: Abstract. It has been suggested that the maturational stage of oocytes at time of insemination influences the sex ratio of resulting embryos. However, there are very few reports concerning the relationship between the maturation culture period of oocytes and the sex ratio of resulting embryos. The objective of this study was to investigate the effects of in vitro maturation culture period for bovine oocytes on the sex ratio of in vitro produced blastocysts using a novel technique of loopmediated isothermal amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 18 publications
(28 reference statements)
3
30
0
1
Order By: Relevance
“…However, examination of pronuclear formation after fertilization failed to indicate a decline in fertilization rate in oocytes inseminated with aged sperm. It may be, therefore, that the reduction in cleavage rate in oocytes inseminated with aged sperm reflects a delay in fertilization and aging of the oocyte [34]. It is also possible that aging damaged the sperm centriole so that syngamy was compromised.…”
Section: Embryo Characteristics As Affected By Sperm Damagementioning
confidence: 99%
“…However, examination of pronuclear formation after fertilization failed to indicate a decline in fertilization rate in oocytes inseminated with aged sperm. It may be, therefore, that the reduction in cleavage rate in oocytes inseminated with aged sperm reflects a delay in fertilization and aging of the oocyte [34]. It is also possible that aging damaged the sperm centriole so that syngamy was compromised.…”
Section: Embryo Characteristics As Affected By Sperm Damagementioning
confidence: 99%
“…Several hypotheses have been addressed trying to explain this finding. Differences have been found regarding culture media conditions [12,13], the maturation culture period of the oocyte [1], sperm damage [4] and epigenetic events which may modulate the difference between speed of development, metabolism and transcription, observed during preimplantation development between male and female embryos [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors have been reported to influence sex ratio in cattle, including 1) timing of insemination in vivo [1][2][3], 2) the maturational state of the oocyte at the time of insemination in vitro [4][5][6], 3) the duration of gamete coincubation in vitro [7], and 4) the postfertilization culture conditions in vitro [8]. It has been reported that the mammalian female could have a preconceptual influence on the sex of her offspring, and it has been hypothesized that this influence could go some way toward accounting for the reported lower fertility following insemination with sex-sorted sperm [9].…”
Section: Introductionmentioning
confidence: 99%